Optimasi Kecepatan Disintegrasi Tablet Terdisintegrasi Cepat (Fast Disintegrating Tablet) Domperidon dengan Superdisintegran Sodium Starch Glycolate - Prabowo, Imam; Iskandarsyah, Iskandarsyah (Majalah Ilmu Kefarmasian, 2011)
Fast disintegrating tablet is one of advanced pharmaceutical technologies. Fast disintegrating tablets is a tablet when placed on the tongue will be instantly disintegrated and releases the drug with the help of saliva. This technology can solve the problem of using oral drug in patients such as pediatrics, geriatrics or in circumstances where the patient can not swallow tablets conventionally with the help of water. The purpose of this study was to optimize the speed of disintegration in fast disintegrating tablet formulations both with varying concentrations of sodium starch glycolate. Optimization the speed of disintegration was done by using sodium starch glycolate with concentration of 8%, 12% and 16% and then disintegration time was tested. After the optimum speed decided, the next step was optimizing the taste using various manitol concentration of 32%, 36% and 40% and evaluation of the taste was conducted by using hedonity test and analyzed with SPSS prog. Disintegration of good fast disintegrating tablet was 27 ± 1 second. The best disintegration time was achieved in tablet using sodium starch glycolate of 16%.